2013
DOI: 10.17221/479/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the origin on selected determinants of the quality of pork meat products

Abstract: Garbowska B., Radzymińska M., Jakubowska D. (2013): Influence of the origin on selected determinants of the quality of pork meat products. Czech J. Food Sci., 31: 547-552.In recent years, great attention has been paid to the quality of eaten meat and its products. There have been launched a lot of promotional campaigns aimed at providing opportunities for the consumption of traditional products. Based on the experiment, a significantly higher protein content was found in sausages produced by large producers (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Typically, traditional meat products often have high fat and salt contents in comparison with conventional products (Garbowska, Radzymińska, & Jakubowska, 2013;Halagarda, Kȩdzior, Pyrzyńska, & Kudełka, 2018). In addition, smoking has been used for centuries for the preservation of meat in some European regions.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, traditional meat products often have high fat and salt contents in comparison with conventional products (Garbowska, Radzymińska, & Jakubowska, 2013;Halagarda, Kȩdzior, Pyrzyńska, & Kudełka, 2018). In addition, smoking has been used for centuries for the preservation of meat in some European regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the average protein content in Silesian, Krakow and frankfurter sausages determined by the cited authors was at the level of 11.29–19.51%, water at the level of 52.40–65.95% and fat at 15.61–3.70%. In studies conducted by Halagard et al [ 42 ] on selected sausages from traditional and conventional productions, it was shown that the average water content ranged from 44.73 g/100 g to 60.14 g/100 g, proteins between 11.35 g/100 g and 24.3 g/100 g and fat from 21.80 g/100 g to 26.39 g/100 g. Grabowska et al [ 43 ] in their research, on the other hand, obtained a higher average protein content in traditional smoked products (21.26%) and in local products (20.06%) compared to the amounts of these ingredients determined in sausages in the author’s research ( Table 2 ). In turn, Halagarda et al [ 44 ], analysing hams from traditional and conventional productions, showed that traditional hams are characterised by the highest nutritional value among the analysed product groups.…”
Section: Resultsmentioning
confidence: 99%
“…Hams studied by Grześkowiak et al [26] contained on average 3.51% of fat. Fat content in traditional hams analyzed by Grabowska et al [25] amounted to 16.25% on average. This value is significantly higher than that obtained in the present study (8.56%).…”
Section: Fatmentioning
confidence: 91%
“…Cooked hams analyzed by Szmańko et al [22] also contained more sodium chloride than the products of all the groups studied, from 3.0% to 3.59%. Grabowska et al [25] obtained an average of 2.9% sodium chloride content in traditional hams. Smoked hams tested by Florek et al [23] were characterized by an average salt content of 2.7%, a value close to the maximum obtained in these studies.…”
Section: Sodiummentioning
confidence: 98%